Chemical Constituents, Larvicidal Effects and Radical Scavenging Activity of Tetracera breyniana Schltdl. (Dilleniaceae) - Cinthia C. de Limaa, Rosangela P. Lyra Lemosb, Lucia M. Conservaa (Journal of Applied Pharmaceutical Science, 2013)
Extracts and fractions from the leaves and stems of Tetracera breyniana Schltdl. were evaluated against the fourth instar Aedes aegypti larvae and ability to scavenge free radicals. Fractions that provided the best results were fractionated on silica gel column to afforded three flavonoils (quercetin, 7-O-methylquercetin and 7-O-methylkaempferol) and two terpenoids (β-sitosterol and betulinic acid). These compounds were identified on basis of their physical and NMR spectral data and by comparison with literature data. With exception of quercetin, all other compounds are been described for the first time in the investigated species. In the larvicidal assays, when compared to synthetic insecticide Temephos, only hexane fraction from stem was effective (LD50 72.08 µg/mL). In the DPPH assays, EtOAc fractions from the leaves (CI50 74.15 ± 14.73 µg/mL) and stem (IC50 39.87 ± 13.46 µg/mL), of which quercetin was isolated, showed the best results when compared with the positive standards used while CHCl3 fractions of both plant parts, of which methylated flavonols were isolated, showed only a moderate activity. Possibly these constituents are responsible in part for the radical scavenging activities observed. Subsequently, evaluation of all isolated compounds will be needed to confirm the active component.
Keywords: Tetracera breyniana, Aedes aegypti